Peroxisome proliferator-activated receptors alpha and beta mediate the anti-inflammatory effects of the cyclopentenone prostaglandin 15-deoxy-Δ12, 14-PGJ2 in fish granulocytes. (November 2022) - Gómez-Abellán, Victoria; Pérez-Oliva, Ana B.; Cabas, Isabel; Hermi, Fatma; Arizcun, Marta; García-Moreno, Diana; Sepulcre, María P.; Mulero, Victoriano
Abstract: Prostaglandins (PGs) are highly reactive small lipophilic molecules derived from polyunsaturated fatty acids of the cell membrane and play a key role in the resolution of inflammation processes. 15-deoxy-Δ 12, 14 -PGJ2 (15dPGJ2 ) is a cyclopentenone PG (CyPG) of the J series with anti-inflammatory, anti-proliferative and pro-apoptotic effects. This CyPG can signal through: (i) the PGD2 receptor (DP2) and peroxisome proliferator-activated receptor γ (PPARγ) or (ii) by covalent binding to protein nucleophiles, such as, thiols groups of cysteine, lysine or histidine via a Michael addition reaction, modifying its structure and function. In this work we show that acidophilic granulocytes (AGs) of gilthead seabream ( Sparus aurata L.), the functional equivalent to mammalian neutrophils, constitutively expressed ppara, pparb and pparg genes, the latter showing the highest expression and up-regulation when stimulated by bacterial DNA. In addition, we tested the ability of 15dPGJ2, and its biotinylated analog, as well as several PPARγ ligands, to modulate reactive oxygen species (ROS) and/or cytokines production during a Toll like receptor (TLR)-mediated granulocyte response. Thus, 15dPGJ2 was able to significantly decrease bacterial DNA-induced ROS production and transcript levels of pparg, interleukin-1β (il1b) and prostaglandin-endoperoxide synthase 2 ( ptgs2) . In contrast, its biotinylated analog was less potent and a higher dose was required to elicit the same effects on ROS production and cytokine expression. In addition, different PPARγ agonists were able to mimic the effects of 15dPGJ2 . Conversely, the PPARγ antagonist T007097 abolished the effect of 15dPGJ2 on DNA bacterial-induced ROS production. Surprisingly, transactivation assays revealed that both 15dPGJ2 and its biotinylated analog signaled via Pparα and Pparβ, but not by Pparγ. These results were further confirmed by HPLC/MS analysis, where Pparβ was identified as an interactor of biotin-15dPGJ2 in naïve and DNA-stimulated leukocytes. Taken together, our data show that 15dPGJ2 acts both through Ppar activation and covalent binding to proteins in fish granulocytes and identify for the first time in vertebrates a role for Pparα and Pparβ in the resolution of inflammation mediated by 15dPGJ2 . Highlights: Gilthead seabream acidophilic granulocytes expressed ppara, pparb and pparg genes. 15dPGJ2 decreased ROS production and proinflammatory gene expression. Biotinylated 15dPGJ2 was less potent than 15dPGJ2. 15dPGJ2 and its biotinylated analog signaled via Pparα and Pparβ, but not by Pparγ. HPLC/MS analysis identified Pparβ as an interactor of biotin-15dPGJ2 .